Multivariate analysis: geography, demographics, and Texas’ post-COVID education - Tang, Shifang; Wang, Zhuoying; Zhang, Lei; Jimenez, David D. (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study examines the impact of geographic locale on educational outcomes in Texas, focusing on the post-COVID-19 educational landscape. The study evaluates the impact of geographical location on the educational outcomes of eighth-grade students by analyzing STAAR test scores as indicators of academic achievement while adjusting for previous academic results and demographic factors. A sample of 1,145 public school districts across Texas was analyzed, encompassing city, suburban, town, and rural settings. The findings indicate that while geographic locale has a discernible impact on academic achievement, this effect is moderate and intertwined with demographic factors. The research found that rural students unexpectedly outperformed their urban counterpart’s post-pandemic, controlling for their pre-pandemic performance. However, the persistent lower performance in urban districts emphasizes the need to reevaluate educational dynamics. The integration of demographic variables reveals that while they mitigate the influence of geography, they emerge as strong influencers of academic performance on their own. This underscores the need for policies that address the complex interplay between geographic, demographic, and socio-economic factors to narrow educational disparities. The study suggests that targeted interventions are necessary to address the specific needs of different locales, considering the nuanced effects of the pandemic on educational equity.